The Consequences of Financial Leverage: Certified B Corporations' Advantages Compared to Common Commercial Firms - Ine Paeleman; Nadja Guenster; Tom Vanacker; Ana Cristina O. Siqueira (Journal of Business Ethics, 2023)
Firms usually need to attract debt to form and grow, but increasing financial leverage also entails increased risks and costs for stakeholders, such as customers and employees. Accordingly, past research suggests that for common commercial firms (CCFs), which prioritize profits, higher leverage leads to lower sales growth and higher employment costs. However, Certified B Corporations (CBCs) distinguish themselves by having a credible prosocial mission and, therefore, might be better insulated against the adverse effects of higher leverage. Using a European multi-country matched sample of 136 CBCs and 136 CCFs, we find that the negative relationship between leverage and sales growth and the positive relationship between leverage and employment costs are weaker for CBCs than CCFs. Taken together, due to their certified prosocial mission, CBCs enjoy an advantage in debt financing compared to CCFs.
Keywords: 300; B Corp social firms; Entrepreneurial finance; Social entrepreneurship